2015
DOI: 10.5455/medarh.2015.69.409-413
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Retinopathy of Prematurity in Premature Born Children

Abstract: Introduction:Retinopathy of Prematurity (ROP) represent disease of the eye in premature born children which affects immature blood vessels of the retina during their development. The emergence of retinopathy of prematurity depends on the interaction of multiple factors, such as: gestational age, low birth weight, hypoxia, duration of oxygen supplementation, respiratory distress syndrome, twin pregnancy, anemia, blood transfusions, sepsis, intraventricular hemorrhage, hypotension, hypothermia, etc. If remain un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
62
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 12 publications
9
62
1
3
Order By: Relevance
“…Similar associations have been described with central auditory impairment and poor cochlear function . A decreased Apgar score is a risk factor for visual impairment, including retinopathy of prematurity in preterm children and optic nerve hypoplasia . In the present study, a low five‐minute Apgar score was independently associated with sensorineural defects.…”
Section: Discussionsupporting
confidence: 88%
“…Similar associations have been described with central auditory impairment and poor cochlear function . A decreased Apgar score is a risk factor for visual impairment, including retinopathy of prematurity in preterm children and optic nerve hypoplasia . In the present study, a low five‐minute Apgar score was independently associated with sensorineural defects.…”
Section: Discussionsupporting
confidence: 88%
“…The association of ROP was more strongly seen with APGAR at 1 minute (r 2 =0.81) than APGAR at 5 minutes (r 2 =0.61). Similar to ours Alajbejovic J. et al (8) in their study found out that low APGAR at 1 minute (3.20±1.30) and 5 minutes (5.20±1.09) were significantly associated (p=0.002; p=0.001 respectively) with occurrence of ROP. Also, study conducted by Chirico G et al (9) the association of ROP was significantly associated with low APGAR score at 1 minute and 5 minutes (p<0.001; p<0.0001 respectively).…”
Section: Discussionsupporting
confidence: 88%
“…The results of many studies involving aforementioned risk factors were similar to this study and excluding the oxygen supplement policy the only other risk factors determined in this study which can be modified is human breast milk. [1][2][3][4][5][6][7][13][14][15][16][17][18] The effect of human breast milk on ROP development is a controversial issue in the literature. [19][20][21][22][23][24][25] As far as we know, studies about the pathophysiological relationship between ROP and human breast milk are limited.…”
Section: Volume 61 • Numbermentioning
confidence: 99%
“…The results are similar to other developing countries. 2,5,6,16,17 Although approved guidelines for the diagnosis and treatment of ROP were used in our study, these guidelines did not include babies born at the 33rd-34th gestational weeks who needed laser treatment in our study. The National Neonatology and Ophthalmology Clinics of our country released a guideline for ROP screening and treatment in 2016.…”
Section: Volume 61 • Numbermentioning
confidence: 99%
See 1 more Smart Citation